Performance of State University: Choice of Strategic Priorities and Implementation of Good University Governances - Cahyana, Agus; Mulyani, Sri; Sukmadilaga, Citra; Farida, Ida (Migration Letters, 2023)
Advances in science and technology affect all areas of life, including university. Universities must be responsive to uncertainties and rapid changes by setting a choice of strategic priorities and putting them into action in accordance with the principles of good university governance in order to produce quality and competitive university performance. The purpose of this research is to examine the impact of the choice of strategic priorities on the implementation of good university governance, as well as the implications for the quality and competitive performance of state universities. This type of research is descriptive and verificative with explanatory survey methods. The sample size in this study was 50 State Universities (PTN) and using questionnaire distribution as the data collection method to echelon II officials and echelon II equivalents. The data analysis technique used in testing the hypothesis is Partial Least Squares (SmartPLS3.0). The outcomes of this investigation led to a choice of strategic priorities that had a significant positive impact on Good University Governance implementation. Implementation of Good University Governance on state university performance has a significant positive effect. The choice of strategic priorities on university performance has a significant positive effect. The choice of strategic priorities on the university performance